2006
DOI: 10.1063/1.2361172
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pinning and proliferation of matching effects in a superconducting film with a Penrose array of magnetic dots

Abstract: The vortex dynamics in superconducting films deposited on top of a five-fold Penrose array of magnetic dots is studied by means of transport measurements. We show that in the low pinning regime (demagnetized dots) a few periodic and aperiodic matching features coexist. In the strong pinning regime (magnetized dots) a richer structure of unforeseen periodic and aperiodic vortex patterns appear giving rise to a clear enhancement of the critical current in a broader field range.Possible stable vortex configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 12 publications
2
58
1
Order By: Relevance
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 92%
“…6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices. For instance, in order to create a distribution of PCs compatible with zero-field cooling conditions, one should then distribute them with a density gradient, decreasing from the edges toward the center of the sample, as expected for the vortex distribution of a partially penetrated sample in the mixed state according to the Bean model.…”
mentioning
confidence: 92%
“…Using APS incommensurate with vortex lattices results in an elastic deformation of the vortex lattice and thus in an increase in the elastic energy. However, pinning properties of a superconductor can be even improved by using incommensurate APS sites, as recently demonstrated (theoretically 17,18 and experimentally [19][20][21][22] ) for quasiperiodic (QP) tiling APS. The important property of QP APS [17][18][19][20][21][22] is the existence of many built-in periods resulting in flux pinning for various flux densities.…”
Section: Introductionmentioning
confidence: 99%
“…These include square [1][2][3][4][5][6], triangular [7][8][9], rectangular [10][11][12], honeycomb [13,14], spin ice [15,16], quasiperiodic [17][18][19][20] and other geometries [21,22]. In these systems a rich variety of novel vortex crystalline states can form, and there can be transitions between commensurate and incommensurate states as a function of vortex density.…”
Section: Introductionmentioning
confidence: 99%